Epistemological Obstacles Experienced by Indonesian Students in Answering Mathematics PISA Test on the Content Uncertainty and Data - H Rahman; D Suryadi; R Rosjanuardi (Universitas Sebelas Maret, 2017)
The purpose of this research is trying to identify epistemological obstacles which were experienced by Indonesian students in answering PISA test for mathematics literacy content uncertainty and data. Epistemological obstacles was identified by giving a test to the respondent, students of grade 7th and 8th who have studied data representation in the class. Respondents’ work analysed by qualitative method. The result showed that respondents have epistemological obstacles in reading the data, reading between the data, and reading beyond the data. To gain further understanding, some respondents chose to be interviewed.